Avaliação bioquímica e densitométrica dos efeitos do ultra-som terapêutico de 1MHz, na dose de 0,5 OU 1 W/cm², sobre o tecido ósseo de cães - Silveira, Douglas Severo (2007)
Tendineous injuries on distal extremity of members are among the most frequent alterations of the locomotor system in both human and animal clinic-surgical routine and frequently adjuvant therapies are needed for the complete return of the physiological functions. The Therapeutic Ultrasound (TUS) is the most commonly used mode of treating tendineous injuries in rehabilitation clinics. However, due to the lack or the disagreements on specific studies about its effects on bone tissues, the use of TUS on distal regions of members, rich in bone protuberances and areas without muscular covering, always worries the professionals of the medical area. With the intention of clarifying the effects of TUS on bone tissue, 18 dogs were separated randomly into 3 groups, in which they received continuous ultrasonic treatment of 1 MHz for 5 minutes during 20 days on the cranium-distally region of the radio and ulna. According to the pre-determined groups, the frequency of TUS applied was of 0.5 or 1 W/cm2. The serum levels of total proteins, albumin, total calcium, ionic calcium, phosphates, alkaline phosphatase and bone alkaline phosphatase, were measured before the beginning of the therapy and after days 4, 7, 11, 14 and 20 of the treatment. The treated regions were also radiographed for analysis of bone densitometry in radiographic images before the therapy and at the end of the treatment. The laboratory exams detected normal serum levels for the main items researched, excepted for albumin which was inferior to the reference values. The statistic analysis of the results obtained show that the TUS caused alteration on the mineral bone metabolism and on the activity of the osteoblasts, especially on the first 7 days of the application, but did not alter the mineral bone density, no matter what dose was used (0.5 or 1 W/cm2). One can conclude that for the parameters in the experiment, TUS in regions of bone protuberances or deprived of muscular covering can be applied with safety.